2018
DOI: 10.1038/s41418-018-0158-8
|View full text |Cite
|
Sign up to set email alerts
|

SREBP1, targeted by miR-18a-5p, modulates epithelial-mesenchymal transition in breast cancer via forming a co-repressor complex with Snail and HDAC1/2

Abstract: The progression of localized breast cancer to distant metastasis results in a poor prognosis and a high mortality rate. In this study, the contributions of miRNAs to tumor progression and the regulatory mechanisms leading to their expression alterations were investigated. Using highly lung-metastatic sub-lines from parental breast cancer cells, miRNA expression profiling revealed that the miR-17-92 cluster is significantly downregulated and the miR-18a-5p is the most evidently decreased. Ectopic expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(110 citation statements)
references
References 56 publications
6
101
0
3
Order By: Relevance
“…We showed that the expression of SREBP1 was associated with the tumorigenic properties where it was associated with the EMT makers. Our results were supported by previous studies where increased SREBP1 expression facilitated EMT in breast and colon cancer [26,35]. In addition, studies have reported that SREBP1 is involved in the proliferation of multiple cancers [22,24,34,37].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We showed that the expression of SREBP1 was associated with the tumorigenic properties where it was associated with the EMT makers. Our results were supported by previous studies where increased SREBP1 expression facilitated EMT in breast and colon cancer [26,35]. In addition, studies have reported that SREBP1 is involved in the proliferation of multiple cancers [22,24,34,37].…”
Section: Discussionsupporting
confidence: 92%
“…SREBP1 is a critical transcription factor that controls the expression of genes important for the uptake and synthesis of lipids, such as cholesterol, fatty acids, and phospholipids [32]. Accumulating evidence suggests that SREBP1 facilitates tumor progression, and the upregulation of SREBP1 has often been detected in many cancer types [22][23][24][25][26][27][33][34][35][36]. In this study, we first identified an increased SREBP1 expression in different ESCC cohorts, which was in an inverse relationship with tumor suppressor miR-142-5p.…”
Section: Discussionmentioning
confidence: 75%
“…qPCR, Western blot analysis, IHC, and immunofluorescence qPCR, Western blot analysis, IHC, and immunofluorescence were performed according to standard protocols as previously described (16). Primers were listed in Supplementary Table S1.…”
Section: Plasmids Sirnas and Transfectionmentioning
confidence: 99%
“…After transfection for 48 hours, cells were stained with cell-cycle stabilizing liquid (Multi-Sciences Biotech) or double stained with Annexin V-FITC/ propidium iodide (PI; BD Pharmingen) following the manufacturer's protocols, and analyzed with a flow cytometer (FACScan; BD Biosciences). The transwell system was implemented for cell migration and invasion assay (24 wells, 8 mmol/L pore size; BD Biosciences) as previously described (16).…”
Section: Cell Proliferation Apoptosis and Transwell Assaysmentioning
confidence: 99%
“…Additionally, MitoSOX Red Mitochondrial Superoxide Indicator was used for mitochondrial ROS measurement (Zhao et al, ). After t‐BHP treatment, the indicator at a final concentration of 5 µM in diluted in DMEM was added to each well and incubated at 37°C for 10 min in the dark (N. Zhang, Zhang, et al, ). The fluorescence was then measured with fluorescence microscopy.…”
Section: Methodsmentioning
confidence: 99%